2016
DOI: 10.1111/tri.12733
|View full text |Cite
|
Sign up to set email alerts
|

A possible role of microRNAs as predictive markers for the recurrence of hepatocellular carcinoma after liver transplantation

Abstract: Summary With favourable 5‐year survival rates up to 75%, liver transplantation (LT) is the treatment of choice for hepatocellular carcinoma (HCC). Nonetheless, tumour recurrence after LT remains a challenge. The aim of this retrospective study was to develop a predictive score for tumour recurrence after LT by combining clinical parameters with HCC biomarkers (microRNA). A microRNA (miRNA) microarray analysis was used to compare miRNA expression patterns in tissue samples of 40 patients with and without HCC re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 55 publications
(77 reference statements)
0
25
0
Order By: Relevance
“…3 . A recurrence [GSE64989 ( 31 )] and two invasive datasets (GSE67139 and GSE67138) were also presented. Student's t-test revealed that miR-124-3p was significantly reduced in HCC compared to normal control samples with GSE 40744 data.…”
Section: Resultsmentioning
confidence: 99%
“…3 . A recurrence [GSE64989 ( 31 )] and two invasive datasets (GSE67139 and GSE67138) were also presented. Student's t-test revealed that miR-124-3p was significantly reduced in HCC compared to normal control samples with GSE 40744 data.…”
Section: Resultsmentioning
confidence: 99%
“…For example, decreased expression of miR-126 in HCC has been correlated with HCC recurrence and poor survival after liver transplantation [30]. In another study, a predictive score combining the expression levels of miR-214, miR-3187 and the Milan criteria was proposed to stratify patients according to their risk for recurrence of HCC and death after liver transplantation [31]. …”
Section: Discussionmentioning
confidence: 99%
“…Circulating miRNA has emerged as one of the most attractive tools for the early diagnosis of cancers [42][43][44]. Some authors have reported that miRNA markers were useful predictors of HCC recurrence after LT [42,[45][46][47]. In the near future, it is expected that the understanding of tumor biology will advance through further analysis of these molecular mechanisms, facilitating individual risk stratification for HCC patients who will benefit from LT [42].…”
Section: Discussionmentioning
confidence: 99%